2021
DOI: 10.1002/jgc4.1469
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling, virtual visits, and equity in the era of COVID‐19 and beyond

Abstract: Overnight, as a result of the COVID‐19 pandemic, telehealth rapidly transitioned from limited application to widespread implementation. The field of genetic counseling was well positioned to make this transition to virtual care since there is generally less of a need for patients to be seen in‐person for physical exams or urgent care. Going forward, virtual visits will presumably become a mainstay in the provision of genetic services and it is anticipated that clinics will adopt “hybrid” models with both in‐pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…25 This testing involves evaluation of a blood specimen and therefore requires infrastructure support to coordinate blood collection, which may be challenging in the COVID-19 pandemic and postpandemic era since much of genetic evaluation has shifted to virtual visits with remote saliva sample collection for GT. 26,27 Mobile phlebotomy and other types of care processes will likely need to be considered more diligently in diverse populations when addressing implementation of RNA testing. 27 In addition, expanded panel testing may be needed to systematically test a larger set of genes among AA men to identify and characterize variants in genes of high or moderate penetrance given that multiple studies have now shown that AA men have a narrow spectrum of germline variants from standard multigene panels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 This testing involves evaluation of a blood specimen and therefore requires infrastructure support to coordinate blood collection, which may be challenging in the COVID-19 pandemic and postpandemic era since much of genetic evaluation has shifted to virtual visits with remote saliva sample collection for GT. 26,27 Mobile phlebotomy and other types of care processes will likely need to be considered more diligently in diverse populations when addressing implementation of RNA testing. 27 In addition, expanded panel testing may be needed to systematically test a larger set of genes among AA men to identify and characterize variants in genes of high or moderate penetrance given that multiple studies have now shown that AA men have a narrow spectrum of germline variants from standard multigene panels.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Mobile phlebotomy and other types of care processes will likely need to be considered more diligently in diverse populations when addressing implementation of RNA testing. 27 In addition, expanded panel testing may be needed to systematically test a larger set of genes among AA men to identify and characterize variants in genes of high or moderate penetrance given that multiple studies have now shown that AA men have a narrow spectrum of germline variants from standard multigene panels. [14][15][16][17] Genetics research findings from genomewide association studies and large population studies also provide insights into the PCA germline spectrum regarding common variants and need further study to determine the clinical role in AA men.…”
Section: Discussionmentioning
confidence: 99%
“…Lower socioeconomic status contributes to an inability to afford the travel to the available genetic counseling location and/or lack of resources to follow through with virtual counseling. Virtual genetic counseling services have been available for years; however, with the COVID-19 pandemic, the benefits of virtual counseling have become very apparent [ 19 ]. The importance of recognizing patients who cannot carry this financial burden is crucial because they are at risk of being lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, an aspect of physician support that will be critical as we move towards a population-based screening model is effective integration of genetic information in the EHR ( 39 43 ). Additionally, telemedicine and telephone delivery strategies (expanded since the onset of the COVID-19 pandemic) offer the opportunity to expand accessibility of genetic counseling services ( 44 , 45 ), although reported success of these types of interventions varies ( 2 ) and concerns about equity in access remain ( 46 ).…”
Section: Solutions From Existing Literaturementioning
confidence: 99%